Performance Analysis of a Civilian GPS Position Authentication System. Issue 4 (10th December 2013) - Li, Zhefeng; Gebre‐Egziabher, Demoz
ABSTRACT A position authentication method utilizing the white‐noise‐like GPS spreading codes as tamper proof watermarks is described. In this method a segment of the GPS signal collected by a trusted user (the authenticator) is used as a template. Another user whose position and time report needs to be verified (the supplicant) sends a sample of its signal. The supplicant's sample is compared with the authenticator's template. The absence of a correlation peak between the two signals indicates that the supplicant is using a non‐authentic GPS signal. A correlation peak having a delay that is inconsistent with relative range between supplicant and authenticator indicates a falsification of the position or time report. Analysis, simulation and experimental results documenting the system's performance are presented. These results show that this approach can detect a deceptive position report with a resolution of 15 meters (1‐sigma) or better. Copyright © 2013 Institute of Navigation.